Efectos de la asociación por puentes de hidrógeno en la reducción electroquímica de quinonas. Análisis cuantitativo en base a medidas de potencial y corriente - Gómez Hernández, Martín (Universidad Autónoma Metropolitana, 2004)
The hydrogen bond is a non covalent interaction responsible of molecular recognition between a wide variety of molecules founded in chemical and biological systems. The majority of the studies, on the hydrogen bonds have been principally focused to the use of this kind of interactions for the design of new molecular systems. Generally, the characterization of hydrogen bonds is carried out with spectroscopic techniques. However, recent developments include electrochemical methods which allow the characterization in-situ of electrochemically generated charged species interacting with hydrogen bond donor molecules. In order to obtain thermodynamic information about the association processes, e. g. equilibrium constants, some nernstian models based on half-wave potential variations are used. In this work, divided in three chapters, it is presented the application of cyc lic voltammetry as a very useful method to characterize the hydrogen bonding association process between two molecules. It is proposed a new methodology of characterization of hydrogen bonding interactions between the reduced states Q - and Q2- of a family of quinones, Q, with different hydrogen bond donors such as the mono-alcohols and diols. The model proposed here is based on the intervention of successive association equilibria whose extent depends on the concentration of the hydrogen bond donor (DH). The analysis of the half-wave potential variation as a function of the concentration of DH allow thus to determine the overall stoichiometry as well as each one of the successive association equilibrium constants. In general, the quinone dianion Q2- is associated with a greater number of molecules of DH than the semiquinone Q - , and it was established that the association constants between Q - and Q2- with the diols are higher than in the case of the mono-alcohols. The values of these constants depend on the quinone basicity, sterical effects and the number of a-hydrogens present in the quinone nucleus. It was also established that in the case of a-phenolic quinones, the intervention of intramolecular hydrogen bonds stabilize the reduction states of the quinone giving rise to a more easy reduction. From the analysis of the effect of temperature on the association processes, it was obtained that the entropic factor is more important for the second reduction step (Q - /Q2- ) than for the first one. It was demonstrated that the entropy value of the reduction step is increased toward more negative values with the increase of the concentration of methanol as hydrogen bond donor; this behaviour is related with the participation of the hydrogen bonding association processes coupled with the electron transfer steps. The solvent properties determine the degree of solvation of DH, the supporting electrolyte ions and the quinone reduction intermediates. The less polar solvent dichloromethane, promotes in major degree the hydrogen bonding association between Q·- and Q2- with DH; meanwhile the more polar solvent and hydrogen bonding acceptor, dimethylsulfoxide, allows the strong solvation of all the chemical species provoking a diminution in the values of the association constants. In order to characterize the association process between neutral species, it has been proposed a model based in voltammetric peak current measurements. From the variation of current intensity of the reduction process of benzoquinone, it was determined the value of the association constant for the benzoquinone-benzoic acid BQ(HBz) and benzoquinone-phtalic acid BQ(HFt) complexes. The difference between these values of association constant is related with the acidity constants of these carboxylic acids. From theoretical calculations, it was determined that the formation of the complex BQ(HBz) is promoted by two-hydrogen bonding interactions. This kind of electrochemical study and characterization is important because it can be used to obtain a better understanding of the role of quinones as electron carriers in photosynthetic processes and cellular respiration mechanisms. In this way, the modulation of the redox reduction potential by hydrogen bonding interactions with weak proton donors, contribute also to a better description of the effect of the cellular protic medium on the quinone redox potentials, favouring or inhibiting the electron transfer processes.; El enlace por puente de hidrógeno es una interacción molecular de tipo no covalente y se presenta ampliamente en sistemas químico-biológicos formando parte del reconocimiento molecular. En la actualidad, la mayoría de los estudios sobre los enlaces de hidrógeno están orientados a utilizar este tipo de interacciones para el diseño de nuevos sistemas moleculares. La caracterización del enlace por puente de hidrógeno se realiza normalmente con técnicas espectroscópicas. Sin embargo, actualmente se han implementado estrategias alternas que incluye el uso de las técnicas electroquímicas, que permiten caracterizar las interacciones por puentes de hidrógeno en las que se involucran especies cargadas (iones generados in-situ). Para acceder a la información termodinámica de los procesos de asociación se recurre a modelos nernstianos basados en variaciones de potencial. En este trabajo, que consta de tres capítulos, se presenta la aplicación de la voltamperometría cíclica como un método para caracterizar la asociación por puentes de hidrógeno entre dos moléculas. Se propone una metodología para caracterizar la asociación por puentes de hidrógeno, entre las especies reducidas de una familia de quinonas Q - y Q2- con diferentes mono-alcoholes y dioles. El modelo propuesto se basa en equilibrios de asociación sucesivos que dependen de la concentración del donador del puente de hidrógeno (DH). El análisis de la variación de potencial permite determinar tanto el valor de la estequiometría como el de las constantes de equilibrio de los procesos de asociación. En general, la especie Q2- se asocia a un número mayor de moléculas de DH respecto a la especie Q - ; y las constantes de asociación entre Q - y Q 2- con los dioles son mayores a las obtenidas con los mono-alcoholes. El valor de las constantes de asociación depende de la basicidad, efectos estéricos y del número de hidrógenos alfa presentes en el núcleo de la quinona. Los productos de reducción de las a-fenol-quinona, pueden formar puentes de hidrógeno intramoleculares que favorecen el proceso de reducción. Se evaluaron los cambios de entropía involucrados en el proceso de reducción de las quinonas, encontrando que el cambio entrópico es mayor para el segundo proceso de reducción (Q - /Q2- ). Se demuestra también que el valor de la entropía de la reacción de reducción, se vuelve más negativa al incrementarse la concentración de MeOH; este comportamiento está relacionado con el proceso de asociación por puentes de hidrógeno. Las propiedades del disolvente determinan el grado de solvatación tanto del DH, de los iones del electrolito y de los intermediarios de reducción de las quinonas. El diclorometano es el que más favorece la asociación por puentes de hidrógeno de Q·- y Q2- con DH; mientras que el dimetilsulfóxido, al solvatar fuertemente a todas las especies químicas, origina una disminución en el valor de las constantes de asociación. Para caracterizar el proceso de asociación entre especies neutras, se ha propuesto un modelo basado en corrientes de pico voltamperométrico. A partir de la variación en las corrientes de reducción de la quinona, se determinó el valor de las constantes de asociación de los complejos benzoquinona-ácido benzóico BQ(HBz) y benzoquinona-ácido ftálico BQ(HFt). La diferencia en los valores de constantes de asociación está relacionada con las constantes de acidez del ácido carboxílico. A partir de cálculos teóricos se determinó que la formación del complejo BQ(HBz), se encuentra favorecida por dos interacciones tipo puente de hidrógeno. Este tipo de estudio y caracterización por vía electroquímica es importante por el hecho de que las quinonas participan como acarreadores de electrones en procesos fotosintéticos y de respiración celular. De esta manera, la modulación del potencial redox a través de la formación de puentes de hidrógeno, con donadores de protones débiles, contribuye a una mejor comprensión del efecto del medio prótico celular sobre los potenciales óxido/reducción de la quinona, al favorecer o inhibir los procesos de transferencia de electrones.